PATOGEN BACTERIA AND VISCERAL ORGAN WEIGHT OF NATIVE CHICKEN IN FEED HERBAL SUPPLEMENTATION - Anggraini, Apriliana Devi; Utari, Tri; Widodo, Wahyu; Susanto, Adi; Rahayu, Imbang D. (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2024)
This study aims to determine the effect of herbal supplementation as a feed additive, through feeding, on the relative weight of visceral organs and the number of pathogenic bacteria in the small intestine and IOFC of ayam kampung. The method used was the experimental method, which consisted of 2 treatment groups, namely group T0 (chickens were only given basal feed, without the addition of herbs) and group T1 (chickens were given basal feed and additional of 1% herbs). Each group consisted of 50 cross-breeding ayam kampung, namely Joper and KUB. The variables measured were the relative weight of the visceral organs (heart, pancreas, liver, spleen and bursa of Fabricius) and the number of pathogenic bacteria in the small intestine (Clostridium, Staphylococcus, Mycobacterium, Pasteurella). The results showed that the administration of 1% herbs to Joper and KUB did not affect the relative weight of the visceral organs tested and no pathogenic bacteria were found in the small intestine in both Joper and KUB chickens. The conclusion that can be drawn from this study is that 1% herbal supplementation as a feed additive has a positive effect on the health of the heart, digestive glands, lymphoid glands, and no pathogenic bacteria are found in the small intestine of ayam kampung, both Joper and KUB